If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(x+7)=-2(3x-2)+8x
We move all terms to the left:
-2(x+7)-(-2(3x-2)+8x)=0
We multiply parentheses
-2x-(-2(3x-2)+8x)-14=0
We calculate terms in parentheses: -(-2(3x-2)+8x), so:We get rid of parentheses
-2(3x-2)+8x
We add all the numbers together, and all the variables
8x-2(3x-2)
We multiply parentheses
8x-6x+4
We add all the numbers together, and all the variables
2x+4
Back to the equation:
-(2x+4)
-2x-2x-4-14=0
We add all the numbers together, and all the variables
-4x-18=0
We move all terms containing x to the left, all other terms to the right
-4x=18
x=18/-4
x=-4+1/2
| 2(2m-3)=7(m+6) | | 26+y=16 | | -v+9v=6v+3 | | 6x-64=4x-32 | | x-5x-10=5+2x-7 | | 3w+6+2w=1 | | -4+6r=8 | | 14.8x=30.2 | | 2+24x=25x | | -4(9-t)=0 | | 2(3a+4)=17 | | 8(3x+9)=6x+252 | | 25m+700=6700 | | x²+10x+20=0 | | 6x+2x+34=58 | | -5/9=x/18 | | b/7=2.5 | | -7(n+2)=-14-14n | | 11r-r-r-3=15 | | 98x+451=36x+1195 | | 10+2=4(7x-3) | | 28x=-35 | | -2x-4-3x=-10 | | 5(x+6)=4x+2x-10 | | 4(1-x)x3x=2(x-1) | | 0.5m—3.5=3m+6.5 | | 3q-7=17 | | -b-(13=4b)=-3(5-9b)+2 | | x+2.9=6.3 | | 6+x=-7+2x | | 28+7x=49+7x | | -17(y+3)+6(4y-3)=6(y-3)+14 |